The Debate Over US Public Debt: Overburdened or Overwrought? - Barry Eichengreen (CESifo Forum, 2022)
During the pandemic, governments increased their expenditures drastically. According to IMF projections, the debt-to-GDP ratio in advanced countries will be 18 percentage points higher by the end of 2021 than before the pandemic and 10 percentage points higher in emerging markets. With rising deficits, public debt around the world has reached unprecedented levels (at least compared to peacetime). For this issue of the CESifo Forum, we have invited leading experts to discuss how their countries can deal with this legacy. We cover the US, the European Union as a whole as well as individual countries, and the UK. The authors discuss debt in a historical context and point out structural reasons that have contributed to increasing debt levels even before the pandemic, as well as the challenges arising from an aging society. They evaluate how feasible it is to grow out of debt, reduce future deficits, and how low interest rates can contribute to sustainability. Finally, we present evidence from previous pandemics that fiscal support has helped mitigate the adverse effects on inequality.
Keywords: 330